Analysis of the Implementation of the BLUD Financial Management Pattern at the SPAM UPTD of Tanjungpinang City - Rasyid, Muhammad Iqbal; Chartady, Rachmad; Friassantano, Risgar; Afriyadi; Novrina, Putri Dwi (Indonesian Scientific Publication, 2025)
The purpose of this research is to find out how the implementation of PPK-BLUD and the obstacles in implementing PPK-BLUD in BLUD UPTD SPAM Tanjungpinang City. The implementation of the PPK-BLUD can be seen from the income, expenses and receivables of the BLUD UPTD SPAM Tanjungpinang City. This research method uses qualitative methods. The data used in this study uses primary data such as interviews and direct observation of informants, then this study also uses secondary data such as Regional Revenue and Expenditure Budget Realization Reports, Budget Business Plans and Mayor Regulations.